Impact of high penetration of solar pv output to line loading, voltage and power losses - Kamil K.; Chong K.H.; Hashim H. (World Academy of Research in Science and Engineering, 2023)
This paper presents the impact of high penetration of solar photovoltaic (PV) power plant to the grid on the line loading, voltage and power losses. In this study, the simulation works is done for IEEE 30 bus test system using Power System Simulation for Engineers (PSSE) software with and without solar PV integration. Simulation results show that high PV penetration of solar PV output causes higher line loading, introduce voltage variation and power losses in the network which might disturb the performance of the network. 2019, World Academy of Research in Science and Engineering. All rights reserved.